Prevalence and molecular characteristics of drug-resistant Mycobacterium tuberculosis in Beijing, China: 2006 versus 2012. Issue 1 (December 2016) - Yin, Qing-Qin; Jiao, Wei-Wei; Li, Qin-Jing; Xu, Fang; Li, Jie-Qiong; Sun, Lin; Li, Ying-Jia; Huang, Hai-Rong; Shen, A-Dong
Abstract Background As the epidemic of MDR-TB and XDR-TB becomes increasingly severe, it is important to determine the clinical characteristics and molecular epidemiology of MDR-TB and XDR-TB. Recently, many studies have shown that clinical features and molecular characteristics of drug-resistant strains vary in different geographical areas, however, further information is needed to assess the dynamic evolution of drug-resistant TB. Comparative studies between different time periods are necessary to elucidate the development of drug-resistant TB. Results A total of 255 and 537 strains were collected from Beijing Chest Hospital in 2006 and in 2012, respectively. Drug-resistance rates and mutations associated with resistance to first-line anti-tuberculosis (TB) drugs were compared. The overall rate of drug resistance among strains of TB in 2012 was 54.4 %, significantly higher than that in 2006 (34.9 %, P  < 0.001). Rates of resistance to each first-line drug (isoniazid, rifampicin, streptomycin and ethambutol) and to second-line drug ofloxacin increased significantly from 2006 to 2012. The overall MDR rate also increased significantly from 2006 (14.9 %) to 2012 (27.0 %). The rate of MDR increased significantly between these two time periods in previously treated cases (P  = 0.023) but not in new cases (P  = 0.073), and the rate of XDR was similar in new cases at the two time periods, but was marginally higher in 2012 in previously treated cases (P  = 0.056). Previous treatment was found to be a risk factor for drug-resistant TB, especially for MDR-TB. In addition, the proportion of drug resistant isolates in whichkatG, themabA-inhA promoter, oxyR-ahpC intergenic region, rpoB, rpsL, andembB were mutated was similar in 2006 and 2012, however patterns of mutation in these loci were more diverse in 2012 compared to 2006. Conclusions Our data suggests that the prevalence of drug resistant TB remains high in Beijing, China, and that increasing rates of resistance inM. tuberculosis to all anti-TB drugs should be considered when choosing an optimal anti-TB regimen. Moreover, acquired multi-drug resistance may play a primary role in the MDR-TB epidemic in Beijing, China. Consequently, this highlights the importance of an earlier start to effective and supervised treatment in order to reduce the burden of retreatment.